Incidence and Risk Factors for Retinopathy of Prematurity (ROP) in Biggest Neonatal Intensive Care Unit in Itay Elbaroud City, Behera Province, Egypt - Gaber R (Dove Medical Press, 2021)
Raouf Gaber, Osama A Sorour, Amr F Sharaf, Hisham A Saad Department of Ophthalmology, Tanta University, Tanta, Gharbeya Province, EgyptCorrespondence: Raouf GaberTanta University Eye Hospital, The Faculty of Medicine, El-Gash St. Medical Campus, Tanta, Gharbeya Province, 31527, EgyptEmail Raouf.a.gaber@gmail.comAim of the Work: To evaluate the incidence and risk factors for development of retinopathy of prematurity (ROP) in the biggest neonatal intensive care unit (NICU) in Itay Elbaroud City, Behera province, Egypt.Methods: We studied data of 240 newly born infants with gestational age (GA) ≤ 34 weeks or birth weight (BW) ≤ 2000 g or infants with unstable course who were admitted to the biggest NICU in Itay Elbaroud City, Behera province, Egypt,  between October 1, 2018 and October 31, 2020. There is no standard screening system in Egypt. Furthermore, we had screened babies more than 1500 g, more than 32 weeks and found signs of ROP, so we decided to expand our inclusion criteria to include babies up to 2000 g of birth weight and up to 34 weeks gestational age in addition to older and heavier babies with unstable course in NICUs. Clinical information about perinatal neonates was collected by reviewing medical charts. The main outcomes are the incidence and severity of ROP. The relationship of clinical risk factors and the development of ROP were analyzed.Results: The overall incidence of ROP was 34.1%, and the overall incidence of type 1 ROP was 26.3% of infants. ROP was significantly associated with GA (odds ratio; OR: 6.8; (3.7– 12.3), BW (OR: 4.1; 2.3– 7.3), apnea, supplementary oxygen administration, and thrombocytopenia.Conclusion: The incidence of ROP is high in Itay Elbaroud city, Behera Province, Egypt. Immaturity, low birth weight, low gestational age, oxygen administration, apnea, thrombocytopenia, and jaundice are important risk factors for development of ROP.Keywords: birth weight, gestational age, incidence, retinopathy of prematurity